CHANGES IN THE INCIDENCE OF SHORTENED MUSCLES IN 11 - 15 –YEAR-OLD GIRLS (Fiep Bulletin - online, 2014)
The work brings forward the results of our pedagogical research, the aim of which was to obtain and widen the knowledge on developmental changes in the incidence of shortened muscles of 11 to 15-year-old girls and possibilities of their remedy using compensation exercises during physical education and sport lessons. The objects of our observation were 15 girls of an elementary school in N itra, who were subject to our observation in the consecutive 6th, 7th, 8th and 9th forms. Totally 5 measurements of muscular imbalance and gait were realized. Between measurements No. 2 and 3 an experimental factor was implemented during the period of 4 months. The experimental programme focused on three most frequently shortened muscles and the following muscle groups: knee flexors, musculus rectus femoris and m. quadratus lumborum. Shortened muscles were examined using the method by Janda (1982), which was modified for the purpose of physical education practice by Thurzová (1992). At the first measurement high incidence of shortened muscles was found in all tested pupils. One year after, an increase in the incidence of 8 out of 11 observed muscles was recorded. Having passed the exercise programme, girls recorded lower frequency of incidence of nine postural muscles by 4 – 30%. Results of the experiment showed positive effect of application of aimed exercises within the compulsory P.E. lessons, which was significantly reflected in the status of the postural muscles. When we omitted the compensation exercises after the termination of the experiment, a significant increase in the incidence of shortened muscles was recorded. By an early and adequate impact of aimed exercises within the P.E. lessons it is possible to affect the incidence of shortened muscles in 11 - 15-year-old girls. Acknowledgements: The contribution is a part of the grant project: VE GA 1/0310/13 „Prevention of malfunctions of motion system in children and possibilities of their remedy“.
Keywords: muscular malfunctions; shortened muscles; qualitative levels